The anti-inflammatory and antioxidant effects of acute consumption of pigmented rice in humans. Issue 12 (15th November 2019) - Callcott, Esther T.; Blanchard, Christopher L.; Snell, Peter; Santhakumar, Abishek B.
Abstract : Coloured rice consumption increased antioxidant status & reduced biomarkers associated with oxidative stress & inflammation. Abstract : The pathogenesis of lifestyle diseases has been significantly correlated to high levels of oxidative stress and pro-inflammation. The antioxidant and anti-inflammatory properties of polyphenols in coloured rice varieties could have potential to neutralize oxidative stress and modulate inflammatory responses. A cross-over design, randomised, dietary intervention human clinical trial was conducted on a pre-screened healthy population ( n = 24) investigating the antioxidant and anti-inflammatory potential of pigmented rice (purple, red and brown) varieties. Post baseline blood samples collection volunteers consumed a serve of cooked pigmented rice. Blood samples were collected at 30-minutes, 1, 2 and 4-hours post rice consumption. A one-week wash-out period between each supplementation bout (rice variety) was conducted. Blood and biochemical parameters were analysed on baseline blood samples. Antioxidant activity, malondialdehyde (MDA) and a pro-inflammatory cytokine panel were analysed on the blood samples collected. Post purple rice consumption, antioxidant activity increased ( p < 0.0001) by 70.5% and maintained elevated for all time points. The red rice variety Yunlu29, significantly ( p < 0.005) reduced MDA levels by 9.2% at the 30-minute time point. Purple rice demonstrated a significant ( p < 0.05) decrease by 4.0% at the 30-minute time point only. Purple rice significantly decreased TNF-α levels at the 1-hour ( p < 0.05) and 4-hour ( p < 0.005) time points by 21.9% and 25.4% respectively. IL-6 concentrations were significantly reduced at 1 and 2-hour post Purple ( p < 0.05; 11.7%) and Yunlu29 (red) ( p < 0.01; 14.1%) consumption respectively. The brown rice variety did not affect any parameters tested. The outcomes of this study, highlight that polyphenols found in pigmented rice may play a key role in targeting specific oxidative stress and inflammatory therapeutic pathways. Pigmented rice varieties may serve as a potential functional food in reducing risk factors associated with lifestyle diseases.